94.2k views
2 votes
What is the inverse equation for the function y=3x-6

2 Answers

3 votes

Answer:

I'm not sure if it's the right answer cuz everyone's saying something else...

but the answer is


y^-1=(x+6)/(3)

Explanation:

to get the solution for the inverse equation is to change x with y.


x=3y-6


x+6=3y-6+6


(x+6)/3=3y/3


(x+6)/(3)=y

and for this is the inverse equation, the exponent for y will be -1.


y^-1=(x+6)/(3)

User Maxlath
by
5.4k points
2 votes
The inverse would be solving for x so the answer is...

y+6/3 = x
User Elsalex
by
5.4k points